An ABC transporter and an outer membrane lipoprotein participate in posttranslational activation of type VI secretion in Pseudomonas aeruginosa. (6th July 2012) - Casabona, Maria G.; Silverman, Julie M.; Sall, Khady M.; Boyer, Frédéric; Couté, Yohann; Poirel, Jessica; Grunwald, Didier; Mougous, Joseph D.; Elsen, Sylvie; Attree, Ina
Summary Pseudomonas aeruginosa is capable of injecting protein toxins into other bacterial cells through one of its three type VI secretion systems (T6SSs). The activity of this T6SS is tightly regulated on the posttranslational level by phosphorylation‐dependent and ‐independent pathways. The phosphorylation‐dependent pathway consists of a Threonine kinase/phosphatase pair (PpkA/PppA) that acts on a forkhead domain‐containing protein, Fha1, and a periplasmic protein, TagR, that positively regulates PpkA. In the present work, we biochemically and functionally characterize three additional proteins of the phosphorylation‐dependent regulatory cascade that controls T6S activation: TagT, TagS and TagQ. We show that similar to TagR, these proteins act upstream of the PpkA/PppA checkpoint and influence phosphorylation of Fha1 and, apparatus assembly and effector export. Localization studies demonstrate that TagQ is an outer membrane lipoprotein and TagR is associated with the outer membrane. Consistent with their homology to lipoprotein outer membrane localization (Lol) components, TagT and TagS form a stable inner membrane complex with ATPase activity. However, we find that outer membrane association of T6SS lipoproteins TagQ and TssJ1, and TagR, is unaltered in a ΔtagTS background. Notably, we found that TagQ is indispensible for anchoring of TagR to the outer membrane fraction. As T6S‐dependent fitness of P. aeruginosa requires TagT, S, R and Q, we conclude that these proteins likely participate in a trans‐membrane signalling pathway that promotes H1‐T6SS activity under optimal environmental conditions.